Pengaruh Pengetahuan Pasien Tentang Hernia dan Kecemasan Pre Operasi Laparaskopi Hernia (Studi Kasus RSU Gading Pluit Jakarta): Penelitian - Evi Deviyana; Bona Dwiramajaya Hartoyo; Diana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A hernia is a weakness of the abdominal muscle wall that passes through a protruding segment of the stomach or abdominal structure. Hernias can also penetrate through several other defects in the abdominal wall. The purpose of this study was to analyze the relationship between knowledge about hernias and anxiety in preoperative laparoscopic hernia patients at Gading Pluit Hospital, Jakarta. This study used a quantitative research type with a correlation descriptive research design with a cross sectional approach which aims to describe the relationship between knowledge about hernias and anxiety in preoperative laparoscopic hernia patients. The population in this study was laparoscopic hernia patients who were going to undergo surgery at Gading Pluit General Hospital, totaling 80 patients. Sampling in this study using purposive sampling with a total sample of 44 respondents. The research results obtained from 44 respondents based on knowledge, there were 89% (39) of patients with good knowledge and 11.5% (5) who had less knowledge. Severe anxiety 82% (36) and less anxiety 18% (8). The statistical test results obtained Pvalue = 0.566 (Pvalue ≤ α = 0.05) so it can be concluded that there is no relationship between knowledge about hernias and anxiety in preoperative laparoscopic hernia patients at Gading Pluit General Hospital Jakarta with OR: 0.547.